Effect of Physician-Delivered Patient Education on the Quality of Bowel Preparation for Screening Colonoscopy - Tze-Yu Shieh; Ming-Jen Chen; Chen-Wang Chang; Chien-Yuan Hung; Kuang-Chun Hu; Yang-Che Kuo; Shou-Chuan Shih; Horng-Yuan Wang (Gastroenterology Research and Practice)
Background. Inadequate bowel preparation is common in outpatients undergoing screening colonoscopy because of unawareness and poor adherence to instruction. Methods. Herein, 105 consecutive outpatients referred for screening colonoscopy were enrolled in this prospective, colonoscopist-blinded study. The patients were assigned to an intensive-education group, with 10 minutes of physician-delivered education, or to standard care. At the time of colonoscopy, the quality of bowel preparation was assessed using the Boston Bowel Preparation Scale (BBPS). The primary outcome was a BBPS score ≥5. The secondary outcomes were the mean BBPS score, insertion time, adenoma detection rate, and number of adenomas detected. Results. We analyzed 39 patients who received intensive education and 60 controls. The percentage of adequate bowel preparations with a BBPS score ≥5 was higher in the intensive-education group than in the control group (97.4% versus 80.0%; P=0.01). The adjusted odds ratio for having a BBPS score ≥5 in the intensive-education group was 10.2 (95% confidence interval = 1.23–84.3; P=0.03). Other secondary outcomes were similar in the 2 groups. Conclusions. Physician-delivered education consisting of a brief counseling session in addition to written instructions improves the quality of bowel preparation in outpatients undergoing screening colonoscopy.